Nutritional composition and antioxidant activity of leaves and rhizomes of Bemban (Donax grandis) grown under glasshouse conditions - Ibrahim, Mohd Hafiz; Mohd Zain, Nurul Amalina (SCIENCEDOMAIN International, 2017)
Aims: The aim of this study is to find out the results of proximate analysis, antioxidant activity and mineral composition of leaves and rhizomes of Donax grandis (locally known as Bemban), an underexploited herbaceous plant that is usually used to cure shingles and snake bites in Malaysia. Study Design: The rhizomes of D. grandis were purchased from Sungai Lembing, Pahang and were propagated for two months in the glasshouse. The seedlings were then planted in soilless medium containing coco-peat, burnt paddy husk and well composted chicken manure in 5:5:1 (v/v) ratio in 25-cm diameter polyethylene bags. Place and Duration of Study: Study was conducted at Department of Biology, University of Putra Malaysia between June 2014 and August 2014. Methodology: Proximate analysis and antioxidant activity were performed using standard AOAC methods. Total phenolics and flavonoids were determined using Folin-Ciocalteu reagent and mineral contents were determined using atomic absorption spectrometry. Results: Generally, the leaves of D. grandis contained the highest values in terms of proximate analysis, antioxidant activity and minerals compared to the rhizomes. The results indicated that Donax grandis was rich in lipids, carbohydrates and total ash. The high amount of total ash (34.21%) suggests a high-value in terms of mineral composition comprising of potassium, sodium, magnesium and calcium as the main elements. The total phenolics, flavonoids, ascorbic acid, DPPH and FRAP values in the leaves were found to be higher (7.12 mg GAE/ g dry weight, 3.21 mg rutin/g dry weight, 1.27 mg/g, 58.2% and 515.21 mmol Fe 2+/g) in comparison to the rhizomes. The DPPH and FRAP showed a strong positive correlation with total phenolics, flavonoids and ascorbic acid indicating that the antioxidant effect might be related to these secondary metabolites. Conclusion: The present study indicated that D. grandis leaves would serve as a rich source of energy, antioxidants as well as micronutrients for human consumption.